1957
DOI: 10.1161/01.res.5.3.230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise and Coronary Artery Narrowing on Coronary Collateral Circulation

Abstract: The effect of chronic coronary arterial narrowing on the coronary collateral circulation has been studied in rested and exercised dogs. The data indicate that moderate and severe arterial narrowing results in extensive collateral development proportional to the degree of narrowing, further that exercise leads to even greater anastomoses. The results also show that while mild arterial narlowing fails to initiate collateral growth by itself, the addition of exercise promotes an effective collateral circulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
3

Year Published

1959
1959
1982
1982

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(44 citation statements)
references
References 3 publications
2
39
0
3
Order By: Relevance
“…This technique allowed completed occlusion or complete release of coronary blood flow within less than 0.1 s. After all recording instruments were connected, a 60-s coronary artery occlusion was produced while lead II of the electrocardiogram was monitored. Only dogs which exhibited significant ST segment elevation, as well as increased heart rate, indicating absence of an effective coronary collateral circulation which might impair the ischemic stimulus produced by coronary occlusion during subsequent studies were used for this study (11). Three of the dogs tested failed to manifest these indications of myocardial ischemia during a 60-s occlusion and were consequently not used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…This technique allowed completed occlusion or complete release of coronary blood flow within less than 0.1 s. After all recording instruments were connected, a 60-s coronary artery occlusion was produced while lead II of the electrocardiogram was monitored. Only dogs which exhibited significant ST segment elevation, as well as increased heart rate, indicating absence of an effective coronary collateral circulation which might impair the ischemic stimulus produced by coronary occlusion during subsequent studies were used for this study (11). Three of the dogs tested failed to manifest these indications of myocardial ischemia during a 60-s occlusion and were consequently not used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that exercise conditioning in rats increases their coronary vascularity (6), maximum coronary blood flow, and myocardial 02 consumption (7), and that exercise in dogs with coronary stenosis promotes coronary collateral development (8). Furthermore, it has been reported that after conditioning, patients with coronary heart disease can reach higher values of heart rate and systolic blood pressure before angina develops during exercise (4,9).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that physical training promotes coronary collaterals was stimulated by the report of Eckstein,27 in which the circumflex coronary artery of dogs was narrowed. Half of the dogs were exercised and the others remained sedentary.…”
Section: Collateral Development With Chronicmentioning
confidence: 99%